Increased Prevalence of NLRP3 Q703K Variant Among Patients With Autoinflammatory Diseases: An International Multicentric Study - Theodoropoulou, Katerina; Wittkowski, Helmut; Busso, Nathalie; Von Scheven-Gête, Annette; Moix, Isabelle; Vanoni, Federica; Hengten, Veronique; Horneff, Gerd; Haas, Johannes-Peter; Fischer, Nadine; Palm-Beden, Katharina; Berendes, Rainer; et al. (Frontiers in Immunology, 2020)
Background: The NLRP3 inflammasome has been recognized as one of the key components of innate immunity. Gain-of-function mutations in the exon 3 of NLRP3 gene have been implicated in inflammatory diseases suggesting the presence of functionally important sites in this region. Q703K (c.2107C>A, p.Gln703Lys, also known in the literature as Q705K) is a common variant of NLRP3, that has been considered to be both clinically unremarkable or disease-causing with a reduced penetrance. Objectives: We aimed to investigate the potential genetic impact of the NLRP3 variant Q703K in patients with recurrent fever presenting with two autoinflammatory diseases: PFAPA (periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis) and CAPS (cryopyrin-associated periodic syndrome), as well as with undefined autoinflammatory disease (uAID). Methods: This is an international multicentric observational retrospective study characterizing the clinical phenotype of patients presenting with recurrent fever suspected to be of auto-inflammatory origin and where the Q703K NLRP3 variant was found. Monocytes of parents of 6 Q703K+ PFAPA patients were studied and levels of pro-inflammatory cytokines produced by monocytes of Q703K+ and Q703K- parents have been compared by ELISA. Results: We report 42 patients with the Q703K NLRP3 genetic variant: 21 were PFAPA patients, 6 had a CAPS phenotype, and 15 had an uAID. The phenotypes of PFAPA, CAPS and uAID were quite similar between Q703K positive and negative patients with the exception of increased prevalence of pharyngitis in the Q703K positive CAPS population compared to the negative one. The in vitro production of IL-1β was not significantly different between Q703K+ and Q703K- monocytes from asymptomatic parents. Conclusion: The evidence we report in our study shows an increased prevalence of NLRP3 Q703K in patients with autoinflammatory diseases, suggesting an association between the Q703K NLRP3 variant and the risk of PFAPA, CAPS and uAID syndromes. However, we did not show a functional effect of this mutation on the inflammasome basal activity.